An enchantment of ravens - Rogerson, Margaret (Margaret K. McElderry Books, 2017)
Isobel is a prodigy portrait artist with a dangerous set of clients: the sinister fair folk, immortal creatures who cannot bake bread, weave cloth, or put a pen to paper without crumbling to dust. They crave human Craft with a terrible thirst, and Isobel's paintings are highly prized. But when she receives her first royal patron--Rook, the autumn prince--she makes a terrible mistake. She paints mortal sorrow in his eyes--a weakness that could cost him his life. Furious and devastated, Rook spirits her away to the autumnlands to stand trial for her crime. Waylaid by the Wild Hunt's ghostly hounds, the tainted influence of the Alder King, and hideous monsters risen from barrow mounds, Isobel and Rook depend on one another for survival. Their alliance blossoms into trust, then love--and that love violates the fair folks' ruthless laws. Now both of their lives are forfeit, unless Isobel can use her skill as an artist to fight the fairy courts. Because secretly, her Craft represents a threat the fair folk have never faced in all the millennia of their unchanging lives: for the first time, her portraits have the power to make them feel.